If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + -7 + -3h = (h + 14) Reorder the terms: -7 + 5h + -3h = (h + 14) Combine like terms: 5h + -3h = 2h -7 + 2h = (h + 14) Reorder the terms: -7 + 2h = (14 + h) Remove parenthesis around (14 + h) -7 + 2h = 14 + h Solving -7 + 2h = 14 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. -7 + 2h + -1h = 14 + h + -1h Combine like terms: 2h + -1h = 1h -7 + 1h = 14 + h + -1h Combine like terms: h + -1h = 0 -7 + 1h = 14 + 0 -7 + 1h = 14 Add '7' to each side of the equation. -7 + 7 + 1h = 14 + 7 Combine like terms: -7 + 7 = 0 0 + 1h = 14 + 7 1h = 14 + 7 Combine like terms: 14 + 7 = 21 1h = 21 Divide each side by '1'. h = 21 Simplifying h = 21
| 4a-1=8 | | 1m=14 | | 10x-(x-5)=8*(x+1) | | 6h+4=76 | | -8x+7y=1034 | | (4x-14)/x-3=x-2 | | 4=-3+16 | | -6=19 | | -14=a+2 | | 1h+125=1h+110 | | 9x-1.6=-8x+1.1 | | -15y=11 | | y/-15=11 | | y-15=11 | | (3y-5w)(7y+6w-1)= | | y^2-4y-5=x | | 9+4x=2x+33 | | W^3=-5 | | 8(-3x)-5x=-87 | | -4=2(-3x) | | 4(x-7)n=2 | | 5(r-4)r=9 | | 6x-6-5x+1=-2+5 | | 4r+3w+2p=39 | | 5x+2=26+x | | 14x-2-13x-2=-6 | | W^3=(1/343) | | 4x+3y+2z=39 | | 3-6=x-2+9 | | 3-6=x-2+6 | | 3-5=y-7 | | a+4=-10 |